Principles of Transversality in Globalization and Education (Springer Singapore, 2018)
This unique book comprehensively covers the evolving field of transversality, globalization and education, and presents creative, research-based thought experiments that seek to unravel the forces of globalization impacting education. Pursuing various approaches to and uses of transversality, with a focus on the ideas of Félix Guattari, it is the only book of its kind. Specifically, it examines the influence of Guattari at the forefront of educational research that addresses, enhances and sets free activist micro-perspectives, which can counter macro-global movements, such as capitalism and climate change. This book is a global education research text that includes perspectives from four continents, providing a balanced and significant work on globalization in education. 'Guattari's notion of 'transversality' that dates from 1964 that famously emphasises a micro-physics of desire in a material semiology that predates the discourse on globalization. Now for the first time in educational theory Cole and Bradley's collection spells out Principles of Transversality in Globalization and Education in lucid and imaginative terms.' - Michael A. Peters, Professor, University of Waikato. 'Editors Cole and Bradley have assembled a ground breaking collection of essays by international luminaries on the ways in which Guattarian transversality remaps educational theory and practice that will become a touchstone for a new generation of critical educators.' - Gary Genosko, University of Ontario Institute of Technology. 'An important collection of essays that not only illustrate the brilliance of Felix Guattari's mind and the importance of his work (independent of his better known collaborator Gilles Deleuze), but also make an important contribution to the study of global education trends and practices. A valuable text for both students and researchers.' - Ian Buchanan, Founding Editor of Deleuze and Guattari Studies. 'This collection of essay is essential reading for anyone interested in the philosophy of education: drawing on some of the most exciting theoretical ventures of the twenty-first century these thoughtful essays provide new ways of thinking about what transversality might mean in challenging learning environments. To think, teach and learn through the concept of the transversal is to be open to new imaginations of the globe, the self and - most importantly - the generation of relations.' - Claire Colebrook, Professor of English, Penn State University.